Rancang bangun mesin press briket dari bahan serbuk kayu sistem pneumatik menggunakan 5 tabung percetak - Setiawan, Bambang; Rasma, Rasma (Universitas Muhammadiyah Metro, 2019)
At this time the Indonesian people are faced with various kinds of problems in terms of waste, if people have knowledge of the use of waste in the surrounding environment then this problem will be overcome, for example waste originating from coconut shells, wood, sawdust and palm shells that can used as charcoal and biomass fuel. In making briquettes with the dimensions and shape of briquettes that are uniform, then a tool designed with pneumatic technology. Because in pneumatic air pressure can be adjusted as needed. Pneumatic technology is a tool that can work (move) by utilizing air pressure from the compressor. Pneumatic works as movers, regulators, controllers and connect work processes.The advantages of pneumatic work systems are the availability of air that is not limited, easily distributed, flexibility, temperature, safe, clean, transfer of power and speed that is easily set. Based on the results of the design of the briquette maker on the process of making briquettes with a pneumatic system capable of speeding up the production time of briquette production and briquette size of 66 mm diameter and 100 cm height, determining the pressure on making briquettes that are uniform according to the weight and shape of the briquettes. Pressing the pressure of 6 bars produces a planned target product of 5 molding on wood briquette press machine but the results of the sawdust are broken and messy due to lack of adhesive and wood powder must be soft in small particles. Keywords: briquette, pneumatic, and briquette making machine.